Comparative Effectiveness of Different Statins on the Risk of Incident Dementia and the Impact of Gender and Exposure time on Risk Reduction: A Meta-analysis of Observational Studies. - Elgardawi , Maha M.; Othman , Kamilah A.; Mesallati , Arig.M.; Abdelmalik , Aisha M.; Idrise , Doua W. (Libyan Journal of Science &Technology, 2025)
The impact of statins in the prevention of dementia has been a point of debate recently however, the evidence remains controversial. For this reason, we conducted this meta-analysis of relevant observational studies to assess the relationship between statin therapy and the reduction of dementia risk Methods: We systematically searched for relevant studies published from 2000 to 2021 using different scientific search engines. Seventeen original articles, which represent observational studies about the prophylactic effect of statin medications in reducing the risk of all-cause dementia were chosen. We then extracted data from the selected studies and performed meta-analysis of these studies using random effects model. Subgroup and sensitivity analyses were also conducted. Results: About 4,241,469 Participants met the eligibility criteria. Statin users had lowered all caused dementia risk than those non-statin users (RR from 17 studies RR= 0.745, 95% CI = 0.653- 0.849, P =0.000). In subgroup analyses, statins reduced the risk of dementia in both males and females (RR= 0.902, 95%, CI=0.872-0.932, P= 0.00), (RR= 0.889, 95%, CI= 0.794- 0.995, P= 0.04). Moreover, testing different statin formulae has shown that atorvastatin and rosuvastatin have significant effects (aRR=0.686, 95%CI=0.488-0.965, p-value=0.030) and (RR=0.695, 95%CI= 0.553-0.873, p-value=0.002). While simvastatin showed a non-significant effect (an RR= 0.900; 95%, CI=0.792-1.024; P=0.109). concerning exposure time, using statin for more than one year tends to show a significant influence on the risk of dementia (RR= 0.576; 95%, CI= 0.367- 0.903; P= 0.016). Conclusion: This analytical study revealed the great value of using statins in both males and females who are at higher risk of developing dementia. It is highly recommended for conducting a clinical study on high-risk Libyan patients.